1999
DOI: 10.1103/physrevb.59.3651
|View full text |Cite
|
Sign up to set email alerts
|

Detailed investigation of the magnetic phase diagram ofCeRu2Ge2up to 11 GPa

Abstract: The electrical resistivity (T) and transverse magnetoresistivity of magnetically ordered CeRu 2 Ge 2 (T N ϭ8.55 K and T C ϭ7.40 K) was measured as a function of pressure up to Pϭ11 GPa and down to Tϭ30 mK. Pressure first increases T N and suppresses T C. Then a second transition, corresponding probably to a modification of the AFM state, appears at T L ϽT N in the pressure range 3.5Ͻ PϽ7.2 GPa. The long-range magnetic order disappears at a critical pressure P c ϭ8.7 GPa like T N ϰ(P c Ϫ P) m , with mϭ0.71(8). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
73
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(88 citation statements)
references
References 58 publications
14
73
1
Order By: Relevance
“…47 The value is enhanced around 2 T for samples under pressures of 6.5 and 6.9 GPa which are lower than the critical pressure of about 8.7 GPa. The enhancement around 2 T was also attributed to an anomaly associated with H a .…”
Section: Fermi Surface Properties Above the Metamagnetic Transitionmentioning
confidence: 83%
See 1 more Smart Citation
“…47 The value is enhanced around 2 T for samples under pressures of 6.5 and 6.9 GPa which are lower than the critical pressure of about 8.7 GPa. The enhancement around 2 T was also attributed to an anomaly associated with H a .…”
Section: Fermi Surface Properties Above the Metamagnetic Transitionmentioning
confidence: 83%
“…3 and that the CeRu 2 Ge 2 becomes paramagnetic around 7.8 -8.7 GPa. 47,48 We may assume that the substitution of Ge by Si gives nearly the same effect on the magnetic properties as that of pressure. We may also assume that the substitution does not affect the Fermi surface properties significantly except for the chemical pressure effect, because the electronic structures of Si and Ge are similar and the contribution to the electronic structure at the Fermi surface from Si or Ge can be assumed to be small.…”
Section: Magnetic Phase Diagrams Of Cerumentioning
confidence: 99%
“…This is a reasonable assumption for ternary Ce-compounds, crystallizing in the ThCr 2 Si 2 -type of structure as was pointed out in Ref. [6]. We used as a unit cell volume of CePd 2 Si 2 at ambient pressure V 0 = 176.83Å 3 which is the mean value of the literature data [5,28,33,41,42].…”
Section: Discussionmentioning
confidence: 99%
“…The electronic interactions in heavy-Fermion (HF) compounds can be influenced in such a way that high pressure favors the Kondo interaction in Ce-compounds [1,2,3,4,5,6,7,8,9] and the RKKY interaction in Yb-systems [10,11]. Thus, pressure suppresses (favors) long range magnetic order and enhances (weakens) the screening of the localized 4f -electrons.…”
Section: Introductionmentioning
confidence: 99%
“…A few groups have demonstrated the ability to detect phase transitions at low temperatures (tens of mK to tens of K) in heavy fermion compounds up to ∼ 10 GPa. [6][7][8][9][10] In making these measurements, they have shown that qualitative calorimetry inside diamond cells is possible, but it is unclear whether such measurements are quantitatively accurate, even in relative values of specific heat as temperature is varied. In some dynamic high-pressure experiments, pyrometry-based temperature measurements allow calculation of specific heats as a shock wave decays.…”
Section: Introductionmentioning
confidence: 99%